Growth and body composition of children aged 2–4 years after exposure to community mobilisation women's groups in Bangladesh. Issue 10 (15th June 2018) - Fottrell, Edward; Ahmed, Naveed; Nahar, Badrun; Shaha, Sanjit Kumer; Kuddus, Abdul; Grijalva-Eternod, Carlos S; Nahar, Tasmin; Fall, Caroline; Osmond, Clive; Govoni, Virginia; Finer, Sarah; Yajnik, Chittaranjan; et al.
Abstract : Background: Women's groups interventions in Bangladesh reduced neonatal deaths by 38% and improved hygienic delivery, newborn care practices and breast feeding. We explore the longer-term impact of exposure to women's groups during pregnancy on child growth at 2–4 years. Methods: We performed a cross-sectional survey of child anthropometric measures (analysed as z-scores) among children born to women who had participated in the women's groups interventions while pregnant, compared with an age-matched and sex-matched sample of children born to control mothers. Results were stratified by maternal body mass index (BMI) and adjusted for possible confounding effects of maternal education, household asset ownership and, in a separate model, mother-child height difference, a proxy for improved survival of small babies in intervention groups. Results: Data were obtained from 2587 mother-child pairs (91% response). After adjustment for asset ownership, maternal education and potential survival effects, children whose mothers were exposed to the women's group intervention had higher head (0.16 (0.04 to 0.28)), mid-upper arm (0.11 (0.04 to 0.19)), abdominal (0.13 (0.00 to 0.26)) and chest (0.18 (0.08 to 0.29)) circumferences than their control counterparts. No significant differences in subcutaneous fat (subscapular and triceps skinfold thickness) were observed. When stratified by maternal BMI, intervention children had higher weight, BMI and circumferences, and these effects decreased with increasing maternal BMI category. Conclusions: Women's groups appear to have had a lasting, positive impact on child anthropometric outcomes, with most significant results clustering in children of underweight mothers. Observed differences are likely to be of public health significance in terms of the nutritional and metabolic development of children.